Earthquake Exposure and PTSD Symptoms Among Disaster-Exposed Adolescents: A Moderated Mediation Model of Sleep Problems and Resilience - Wang, Shuo; Shi, Xuliang; Chen, Xiaoyan; Zhu, Ya; Chen, Huilin; Fan, Fang (Frontiers in Psychiatry, 2021)
Considerable studies have explored the potential mechanisms between trauma exposure and PTSD, but little is known about the role of sleep problems and resilience in this relationship. To address this research gap, the present study examined whether sleep problems mediated the relationship between earthquake exposure and PTSD symptoms, and whether this mediating process was moderated by resilience. A sample of 1,342 adolescents (Mage=15.54 years, SD=1.26) completed questionnaires regarding earthquake exposure, sleep problems, resilience and PTSD symptoms 12 months after a devastating earthquake in China. After controlling for demographic variables, earthquake exposure was significantly and positively associated with PTSD symptoms, and sleep problems partially mediated this relationship. Tests of moderated mediation further revealed that resilience moderated the relationship between earthquake exposure and PTSD symptoms as well as sleep problems and PTSD symptoms. Specifically, the relationship between earthquake exposure and PTSD symptoms was only signiﬁcant for adolescents with a lower level of resilience; meanwhile, the positive relationship between sleep problems and PTSD symptoms was stronger among low-resilient adolescents. Therefore, sleep-targeted and resilience-based interventions may be effective in alleviating PTSD symptoms resulted from the earthquake.